FRI0386 Increased prevalence of metabolic syndrome is associated to nephrolithiasis but not to the presence of tophus in GOUT patients. (23rd January 2014) - Mello, F.M.; Tomita, F.R.B.; Fuller, R.; Pontes Filho, M.A.G.; Barros, T.B.M.; Prado, L.L.; Augusto, K.L.; Goldenstein-Schainberg, C.
Abstract : Background: Metabolic syndrome (MS) has been frequently associated to gout and, in fact, hyperinsulinemia enhances proximal tubular sodium reabsorption, leading to decreased renal uric acid excretion and hyperuricemia.No data regarding the prevalence of MS in gout subsets according to gout-associated clinical characteristics has been published to date. Objectives: To determine the prevalence of MS in a large cohort of patients with gout followed at a single tertiary center, searching for related risk factors including metabolic profile, nephrolithiasis, reduced urate excretion and the presence of tophus. Methods: This was a cross-sectional study of 158 patients with gout diagnosed according to the ACR criteria. MS was definedaccording to the National Cholesterol Education Program ATP III (NCEP-ATP III) and the International Diabetes Federation (IDF) criteria.Demographic, anthropometric (body mass index - BMI) and clinical data were collected. Fasting serum levels of uric acid, glucose, triglycerides and cholesterol fractions were analyzed by usual laboratory tests.Nephrolithiasis was demonstrated by routine ultrasonography and urate underexcretion was defined as a uric acid clearance lower than 7.5 ml/min. Fisher's exact, chi-square, student's T and Spearman's test were used for statistical analysis and P≤0.05 was considered significant. Results: Mean age of patients was 62.7±12.2 yrs (33 – 90 yrs), and 90.5% were males. Mean BMI was 29.13±5.70 kg/m 2 (19.0 – 55.1 kg/m 2 ). Hypertension was observed in 84.5% of patients, current alcohol consumption in 22.8%, coronary artery disease in 21% and diabetes mellitus in 19%. Mean serum uric acid, fasting glucose, triglycerides, LDL, HDL levels were 6.84 mg/dL, 107.2 mg/dL, 198.7 mg/dL, 116.7 mg/dL, 47.2 mg/dL respectively. Of note, 31% had nephrolithiasis and 52.5% had tophi. Estimated creatinine clearance was 73.15±29.35 ml/min and 86.1% patients manifested urate underexcretion.Remarkably, more than 70% of gout patients had MS (73% and 71% according to NCEP ATPIII and IDF criteria respectively). This increased prevalence of MS was alike in patients with tophaceous and non tophaceous gout, and regardless of uric acid excretionstatus (p>0, 05). In contrast, the prevalence of MS was significantly higher in patients with nephrolithiasis compared to those without this complication (84.7% vs. 65.2%; p=0.026). Conclusions: The elevated prevalence of MS in Brazilian gout patients (almost ¾) is higher than previously reported overall rates of MS in gout worldwide (62.8%) and in control populations (25.4%), suggesting possible interference of, dietary, geographical and/or genetic background. Our demonstration, for the first time, of increasedMS prevalence in gout unrelated to the occurrence of tophus, but associated to nephrolithiasis may suggest shared underlying physiopathologic mechanisms, such as the effect of hyperinsulinemia on the kidneys.Further studies are urged to clarify this relationship and therefore allow improvement of multiprofessional management of gout patients, in order to reduce long-term complications and prevent associated comorbidities. Disclosure of Interest: None Declared